A MULHER ALÉM DO BEM E DO MAL: Malévola e a representação cinematográfica do feminino integrado - MACHADO, Patricia Santos (2016)
A study on the symbolic and self-defining constructions of the Woman in the narrative and the structures of female characters in the Disney Studios production Maleficent (2014) – USA. The plot is inspired on the fairy tale “The Sleeping Beauty in the Wood” but from a feminine standpoint, widening the possibilities of interpretation and allowing for a rupture from the dichotomic paradigm related to the struggle between “Good versus Evil”. This research aims at studying the evolution of the archetypical imaginary constructs of the characters in Maleficent in contrast with female identity in contemporary culture. For that end, the theoretical frame of reference includes the study of social imaginaries through the works of Durand, Edgar Morin and, most notably, Michel Maffesoli; psychoanalytical concepts from the works of de C.G. Jung, Erich Neumann, Marie-Louise Von Franz and Clarissa Pinkola Estés; Stuart Hall’s, Laura Mulvey’s and Gilles Lipovetsky’s theories of Cultural Studies with an emphasis on gender; and also ecofeminism, through the works of authors such as Vandana Shiva and Maria Mies. Our selected theoretical-methodological reference is the Depth Hermeneutics, with a view to the interpretation of the symbolic structure of our study. As a result of this research we verify a process of saturation of identity and symbolic patterns originated in Modernity, and the evolution of new dynamics in mediatic and communication narratives.